FAKTOR-FAKTOR YANG MEMOTIVASI WANITA BERWIRAUSAHA ONLINE DI KOTA MAKASSAR - Ahmad Firman (Jurnal Bisnis dan Kewirausahaan, 2018)
This study aims to determine and analyze the factors that motivate women online entrepreneurship in Makassar. The method of analysis used in this study is multiple regeresi analysis, t test, F test. The research used data collection methods through Observation, Interview, and Questionnaire (Questionnaire). Types The data used in this study are qualitative data and quantitative data sourced from primary and secondary data. The results of this study indicate that all good variables that self-efficacy, tolerance of risk, and the desire to have a free job have a positive and significant impact on motivating women to become entrepreneurs through online business. As for the research of each independent variable, there is also a positive and significant influence on the dependent variable. It can be concluded that each independent variable be it self efficacy, risk tolerance, and desire to feel free work, have positive and significant influence to entrepreneurship desire variable.